Predestined Steady‐State Entanglement under Pure Vacuum Noise. Issue 3 (30th December 2022) - Zhou, Yuebing; Hu, Jiawei; Yu, Hongwei
Abstract: Ever since the seminal work by Yu and Eberly [Phys. Rev. Lett. 93, 140404 (2004)], it has become widely accepted that nonlocal entanglement is more fragile than local coherence, in the sense that even under the influence of pure vacuum noise, the two‐qubit entanglement may end within a finite time, while the single‐qubit coherence always decays exponentially. By contrast, in this paper, it is shown that, for a pair of rotating qubits under pure vacuum noise with appropriate orbital radius and angular velocity, nonlocal entanglement as compared to local coherence is not only more resilient against vacuum noise to be preserved in the steady‐state for initially entangled states, but more importantly is also predestined to be created and be preserved for initially separable states. The generation of predestined entanglement here is essentially different from the dissipative steady‐state entanglement generation in existing schemes insofar as it is inevitably generated in pure vacuum instead of an elaborately designed environment. Abstract : For a pair of rotating qubits under pure vacuum noise, there may exist predestined steady‐state entanglement independent of the initial state, while the quantum coherence of a single qubit under the same condition is doomed to be completely destroyed.